A High-Level Thinking Test on Science Material for Fifth Grade Elementary School Students - I Made Arsana; Ida Bagus Putu Arnyana; I Made Candiasa (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
The quality of the instrument that does not apply high-level thinking skills greatly influences students' ability in high-level thinking, which is still lacking. This study aims to create a high-level thinking test in science for grade V elementary school students. The instrument developed is in the form of a descriptive test consisting of 20 questions on Style material. This study is an R&D study with a Formative Research model. The data analysis technique uses quantitative analysis and inferential statistics. The study subjects were experts and practitioners, teachers and elementary school students. The study results obtained a prototype of a high-level thinking test in science consisting of 1 package of science material in a description. The validity of the test obtained 17 valid items. All valid questions are reliable. The test discrimination index obtained 3 questions in the medium category and 14 in the high category. The test item difficulty index is in the medium category. The test parameters' accuracy level obtained 10 questions in the fit category and 7 in the unfit category. A high logit value indicated students' ability to solve questions. The study concludes that the instrument developed can measure students' high-level thinking skills and be used in the learning process. This research implies that the questions that have been developed can be used by teachers to measure the effectiveness of learning according to student needs.